2005
DOI: 10.1111/j.1445-2197.2005.03388.x
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Assessment of Breast Reconstruction in a Specialist Breast Unit

Abstract: Breast reconstruction undertaken by breast surgeons trained in breast reconstruction and oncoplastic techniques has been performed with an acceptable rate of complications and a high level of patient satisfaction. Satisfaction with breast reconstruction was similar across the four methods of reconstruction used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 62 publications
1
10
0
Order By: Relevance
“…The majority of studies that measured quality of life used generic instruments which may not be able to discriminate between outcomes of reconstruction and mastectomy only 54. Of note, the five studies that did use breast cancer-specific instruments which have been validated in breast cancer patients and shown to be responsive to change,51, 52 found equivalent or poorer outcomes with reconstruction 25, 28–30, 53. Of the studies that measured body image, only one used a disease-specific measure 25.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies that measured quality of life used generic instruments which may not be able to discriminate between outcomes of reconstruction and mastectomy only 54. Of note, the five studies that did use breast cancer-specific instruments which have been validated in breast cancer patients and shown to be responsive to change,51, 52 found equivalent or poorer outcomes with reconstruction 25, 28–30, 53. Of the studies that measured body image, only one used a disease-specific measure 25.…”
Section: Discussionmentioning
confidence: 99%
“…The methods of reconstructive surgery currently practised comprise flap reconstruction, implant reconstruction and a combination of these procedures (Nano et al, 2005). Flap reconstruction involves transferring sections of a woman's own muscle tissue from a remote site in the body to the breast area; procedural risks include loss of blood circulation to the transplanted muscle tissue, infection and abdominal bulges (Clayton & Waller, 1996).…”
Section: Factors Affecting the Breast Reconstruction Decisionmentioning
confidence: 99%
“…51 Many studies have found that method of reconstruction has a limited effect on psychosocial outcomes especially when this is considered over time and following completion of the reconstructive process. 48,50,52 However, there are numerous reports of significant associations between procedure type and satisfaction rates, with autologous tissue-based procedures tending to have higher satisfaction rates than implant-based procedures. 5355 …”
Section: Overview Of Patient-reported Outcomes Research In Breast Recmentioning
confidence: 99%